Instruments of choice for assessment and monitoring diabetic foot: A systematic review - Fernández Torres, Raúl; Ruiz-Muñoz, María; Pérez Panero, Alberto José; García-Romero, Jerónimo; González-Sánchez, Manuel (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Diabetic foot is the most frequent disorder among the chronic complications of diabetes, happening in 25% of patients. Objective clinical outcome measures are tests or clinical instruments that provide objective values for result measurement. The aim of this study was to carry out a systematic review of specific objective clinical outcome measures focused on the assessment and monitoring of diabetic foot disorders. The databases used were PubMed, CINAHL, Scopus, PEDro, Cochrane, SciELO and EMBASE. Search terms used were foot, ankle, diabet*, diabetic foot, assessment, tools, instruments, objective outcome measures, valid*, reliab*. Because of the current published evidence, diabetic neuropathy assessment via sudomotor analysis, cardiovascular autonomic neuropathy and peripheral vascular disease detection by non-invasive electronic devices, wound 3D dimensional measurement, hyperspectral imaging for ulcer prediction and the probe-to-bone test for osteomyelitis diagnosis were highlighted in this study. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Diabéticos - Tratamiento; Diabetes - Complicaciones y secuelas; Diabetes complications; Diabetes; Foot; Ankle; Review; Evidence; Tools; Outcome measures